El orden de Melquisedec, de Calderón de la Barca / estudio y edición. - Urzáiz Tortajada, Héctor. (University of Ottawa (Canada), 1996)
This M.A. thesis offers an annotated edition of Calderon's auto sacramental El orden de Melquisedech. The thesis consists of: (1) an introductory study, composed of: (a) a general survey of the dramatic genre to which the auto sacramental belongs; (b) the date of composition of El orden de Melquisedech; (c) a critical analysis of the auto, with special emphasis on staging and allegory; (d) editing criteria; (e) a bibliography. (2) the edited text of the auto, whose spelling and punctuation have been modernized except where the pronuntiation would be affected. All the changes introduced in the copy-text have been registered in the textual notes. (3) philological notes, where any difficult passage, internal references and biblical, literary and other allusions are explained.
Keywords: Literature, Romance.